Bone metabolism and inflammatory biomarkers in radiographic and non-radiographic axial spondyloarthritis patients: a comprehensive evaluation - Gómez-García, Ignacio; Ladehesa-Pineda, Maria L.; Diaz-Tocados, Juan M.; López-Medina, Clementina; Abalos-Aguilera, Maria C.; Ruiz-Vilches, Desiree; Paz-Lopez, Guillermo; Gonzalez-Jimenez, Andres; Ranea, Juan A. G.; Escudero-Contreras, Alejandro; Moreno-Indias, Isabel; Tinahones, Francisco J.; et al. (Frontiers in Endocrinology, 2024)
Introduction: Axial spondyloarthritis (axSpA) is a heterogeneous disease that can be represented by radiographic axSpA (r-axSpA) and non-radiographic axSpA (nr-axSpA).This study aimed to evaluate the relationship between the markers of inflammation and bone turnover in r-axSpA patients and nr-axSpA patients.Methods: Cross-sectional study of 29 r-axSpA patients, 10 nr-axSpA patients, and 20 controls matched for age and sex. Plasma markers related to bone remodeling such as human procollagen type 1 N-terminal propeptide (P1NP), sclerostin, Tartrate-resistant acid phosphatase 5b (TRACP5b), Receptor Activator of Nuclear Factor Kappa B Ligand (RANKL), and osteoprotegerin (OPG) were measured by ELISA kit. A panel of 92 inflammatory molecules was analyzed by proximity extension assay.Results: R-axSpA patients had decreased plasma levels of P1NP, a marker of bone formation, compared to controls. In addition, r-axSpA patients exhibited decreased plasma levels of sclerostin, an anti-anabolic bone hormone, which would not explain the co-existence of decreased plasma P1NP concentration; however, sclerostin levels could also be influenced by inflammatory processes. Plasma markers of osteoclast activity were similar in all groups. Regarding inflammation-related molecules, nr-axSpA patients showed increased levels of serum Interleukin 13 (IL13) as compared with both, r-axSpA patients and controls, which may participate in the prevention of inflammation. On the other hand, r-axSpA patients had higher levels of pro-inflammatory molecules compared to controls (i.e. IL6, Oncostatin M, and TNF Receptor Superfamily Member 9). Correlation analysis showed that sclerostin was inversely associated with IL6 and Oncostatin M among others. Conclusion: Altogether, different inflammatory profiles may play a role in the development of the skeletal features in axSpA patients particularly related to decreased bone formation. The relationship between sclerostin and inflammation and the protective actions of IL13 could be of relevance in the axSpA pathology, being a topic for further investigation.